Criticizing the Muslim Divorce Tradition in Lombok: An Effort to Control the Women's Rights - Abdullah Abdullah; Hijrah Hijrah; Hery Zarkasih (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
This research aims to identify the divorce tradition in Lombok Muslim life and find solutions to the problems occurring. This is field research using observation, interview, and documentation methods. In this study, the researchers directly observed and interviewed audiences. Moreover, the researchers discovered some problems of Muslim divorce tradition in Lombok Island, namely, the report from a husband to a religious personage or community leader about the divorce between him and his wife. The second problem is pecelekan (bringing back a woman to her parents after her husband has divorced her). The third problem is eliminating the man’s livelihood responsibility after divorcing his wife. In Lombok Island, the divorce can automatically stop the relationship between the husband and wife. In other words, there is no responsibility anymore for a husband after a husband says divorce to his wife. However, separation of spouse by divorce in Islam does not automatically abolish the husband’s responsibilities. The woman in ”˜iddah period still obtains her rights. Nevertheless, in Lombok, divorce causes the divorced wife to lose her rights. This research contributes to finding two solutions to solve these problems. The first way is by socializing intensively with all of society, and the second is through the active role of religious personage to control women’s rights in Lombok society.